Management of Iron-Deficiency Anemia in Inflammatory Bowel Disease: A Systematic Review - Nielsen, Ole Haagen (Medicine (Baltimore), 2015)
Anemia is the most frequent complication of inflammatory bowel disease (IBD), but anemia, mostly due to iron deficiency, has long been neglected in these patients. The aim was to briefly present the pathophysiology, followed by a balanced overview of the different forms of iron replacement available, and subsequently, to perform a systematic review of studies performed in the last decade on the treatment of iron-deficiency anemia in IBD. Given that intravenous therapies have been introduced in the last decade, a systematic review performed in PubMed, EMBASE, the Cochrane Library, and the websites of WHO, FDA, and EMA covered prospective trials investigating the management of iron-deficiency anemia in IBD published since 2004. A total of 632 articles were reviewed, and 13 articles (2906 patients) with unique content were included. In general, oral supplementation in iron-deficiency anemia should be administered with a target to restore/replenish the iron stores and the hemoglobin level in a suitable way. However, in patients with IBD flares and inadequate responses to or side effects with oral preparations, intravenous iron supplementation is the therapy of choice. Neither oral nor intravenous therapy seems to exacerbate the clinical course of IBD, and intravenous iron therapy can be administered even in active disease stages and concomitantly with biologics. In conclusion, because many physicians are in doubt as to how to manage anemia and iron deficiency in IBD, there is a clear need for the implementation of evidence-based recommendations on this matter. Based on the data presented, oral iron therapy should be preferred for patients with quiescent disease stages and trivial iron deficiency anemia unless such patients are intolerant or have an inadequate response, whereas intravenous iron supplementation may be of advantage in patients with aggravated anemia or flares of IBD because inflammation hampers intestinal absorption of iron.